Densidade e estrutura populacional do caranguejo-uçá, "Ucides cordatus" (Linnaeus, 1763) (Crustacea: Brachyura: Ocypodidae), em Cananéia (SP): parâmetros abióticos e níveis antrópicos explicativos - Ferreira, Kimberly Mazagão [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
Mangroves are coastal environments characteristic of tropical and subtropical regions, subject to frequent flooding by the tidal regime. For this reason, they present a great variation in their environmental and biological parameters, which can cause changes in the population density of various organisms. Ucides cordatus is a semi-terrestrial crab that is endemic to mangroves and one of its key species, due to its high biomass and relevant role in nutrient cycling. The influence of environmental and biotic parameters on the density and population structure of mangrove crabs has been poorly addressed in the literature, requiring more comprehensive studies. In addition, the population of U. cordatus on the south coast of the State of São Paulo still has an excellent state of conservation, however, with extraction that inspires care, since this species has biological restrictions, including its reduced rate of growth and seasonal reproduction. In this sense, the best knowledge of the abiotic and biotic parameters on this species would be extremely important. In this context, the objective of the present study is to characterize the density (ind./m²) and size / population structure of U. cordatus in the Municipality of Cananéia (SP), under the influence of abiotic (atmospheric, water and edaphic) and biotic parameters ( mangrove tree vegetation), under different levels of tidal flooding. The assessments were carried out in mangroves of five different fishing sectors of the Cananéia-Iguape Estuarine-Lagoon System, comprising two sampling sub-areas each, differing in terms of tidal flood level (NI), namely: AMA, high mangrove (<NI) ; and AMB, low mangrove (> NI). The density and population structure were obtained in each of these sub-areas, where the level of flooding (NI) was recorded by measuring the maximum level of vertical distribution of the macroalgae at the base of the trunks and pneumatophores of the mangrove trees. The sampling sub-areas were compared to evaluate possible statistical contrasts according to the abiotic parameters (water and sediment) and tree vegetation, in relation to the density and size of U. cordatus. The data were evaluated by simple correlation analysis (Spearman) between independent variables (abiotic and biotic related to tree vegetation) and dependent ones (density and size of uçá crab). The general average density of Cananéia (SP) was 2.28+-1.23 ind./m², showing significant differences in terms of sub-areas, due to the different levels of flooding. The size (LC, carapace width), in turn, averaged 58.4+-18.1mm, behaving in a manner contrary to density, with the largest individuals found in areas of greater flooding and vice versa. The fishing sectors showed significant differences between several factors, such as flood level, granulometric composition, hydrodynamics, cation exchange capacity, macro and micronutrients, tree diameter and height, air temperature, air humidity, among others. As for the extractive potential, the areas of greatest flooding (AMB) showed greater immediate extractive potential (adults LC>60mm) than in the future (LC <60mm LC), the opposite occurring in less flooded areas. The five fishing sectors previously defined for the Municipality of Cananéia showed key differences, indicating the following hierarchical order regarding conservation A> D> B> C> E. Likewise, the differences tend to be clearer when comparing the areas of greatest and a lower level of flooding in relation to the parameters. The density of the crab Ucides cordatus in the region is in accordance with the national standard, as well as the greater presence of individuals in non-commercial size. In this region there is a lower density of crabs in areas of greater flooding, as well as the smaller size of individuals in the same area. In most of the fishing sectors in Cananéia, PEI <PEF was registered, indicating the need for management strategies aimed at resource conservation. The knowledge of this information is of great relevance for fisheries planning policies, assisting in the establishment of conservation and preservation areas, in the implementation of rotation systems and support for management plans.

Os manguezais são ambientes costeiros característicos de regiões tropicais e subtropicais, sujeitos à frequente inundação pelo regime de marés. Por isso, apresentam grande variação em seus parâmetros ambientais e biológicos, que podem propiciar alterações da densidade populacional de vários organismos. Ucides cordatus é um caranguejo semiterrestre que é endêmico de manguezais e uma de suas espécies-chave, por conta de sua elevada biomassa e relevante papel na ciclagem de nutrientes. A influência de parâmetros ambientais e bióticos sobre a densidade e estrutura populacional de caranguejos de manguezais tem sido pouco abordada na literatura, requerendo estudos mais abrangentes. Além disso, a população de U. cordatus no litoral sul do Estado de São Paulo ainda detém excelente estado de conservação, porém, com extração que inspira cuidados, já que esta espécie apresenta restrições biológicas, entre elas sua reduzida taxa de crescimento e reprodução sazonal. Neste sentido, o melhor conhecimento dos parâmetros abióticos e bióticos sobre esta espécie seriam de suma relevância. Neste contexto, o objetivo do presente estudo é caracterizar a densidade (ind./m²) e tamanho / estrutura populacional de U. cordatus no Município de Cananéia (SP), sob influência de parâmetros abióticos (atmosféricos, hídricos e edáficos) e bióticos (vegetação arbórea de manguezal), sob diferentes níveis de inundação pelas marés. As avaliações foram desenvolvidas em manguezais de cinco diferentes setores pesqueiros do Sistema Estuarino-Lagunar de Cananéia-Iguape, compreendendo duas subáreas amostrais cada, diferindo quanto ao nível de inundação pelas marés (NI), a saber: AMA, manguezal alto (<NI); e AMB, manguezal baixo (>NI). A densidade e estrutura populacional foram obtidas em cada uma dessas subáreas, onde o nível de inundação (NI) foi registrado pela medida do nível máximo de distribuição vertical das macroalgas na base dos troncos e pneumatóforos das árvores do manguezal. As subáreas amostrais foram comparadas para a avaliação de possíveis contrastes estatísticos em função dos parâmetros abióticos (água e sedimento) e da vegetação arbórea, em relação a densidade e tamanho de U. cordatus. Os dados foram avaliados por análise de correlação simples (Spearman) entre as variáveis independentes (abióticas e bióticas relacionada à vegetação arbórea) e aquelas dependentes (densidade e tamanho do caranguejo-uçá). A densidade média geral de Cananéia (SP) foi de 2,28+-1,23 ind./m², apresentando diferenças significativas quanto as subáreas, em função dos diferentes níveis de inundação. O tamanho (LC, largura da carapaça), por sua vez, teve média de 58,4+-18,1mm comportando-se de forma contrária à densidade, com os indivíduos maiores encontrados em áreas de maior inundação e vice-versa. Os setores pesqueiros demonstraram diferenças significativas entre vários fatores, como nível de inundação, composição granulométrica, hidrodinâmica, capacidade de troca catiônica, macro e micronutrientes, diâmetro e altura das árvores, temperatura do ar, umidade do ar, entre outros. Quanto ao potencial extrativo, as áreas de maior inundação (AMB) apresentaram maior potencial extrativo imediato (adultos LC>60mm) do que do futuro (LC<60mm LC), o contrário ocorrendo em áreas de menor inundação. Os cinco setores pesqueiros previamente definidos para o Município de Cananéia apresentaram diferenças chave, indicando a seguinte ordem hierárquica quanto a conservação A > D > B > C > E. Da mesma forma, as diferenças tendem a ficar mais claras quando comparadas as áreas de maior e menor nível de inundação frente aos parâmetros. A densidade do caranguejo Ucides cordatus na região está de acordo com o padrão nacional, assim como a maior presença de indivíduos em tamanho não comercial. Nesta região há menor densidade de caranguejos em áreas de maior inundação, assim como o menor tamanho dos indivíduos na mesma área. Na maior parte dos setores pesqueiros de Cananéia registrou-se PEI < PEF, indicando a necessidade de estratégias de manejo que visem a conservação do recurso. O conhecimento destas informações é de grande relevância para políticas de ordenamento pesqueiro, auxiliando no estabelecimento de áreas de conservação e preservação, na implantação de sistemas de rodízio e subsídio a planos de manejo.
Density and population structure of the uçá crab, "Ucides cordatus" (Linnaeus, 1763) (Crustacea: Brachyura: Ocypodidae), in Cananéia (SP): abiotic parameters and explanatory anthropic level
Keywords: caranguejo; densidade; distribuição espacial; estrutura populacional; manguezal; crab; Mangrove; Density; population structure; spatial distribution